A Study of the 21st Century Teaching Competences in Content-Based Instruction Implementation - Mufaridah, Fitrotul; Nurkamilah, Nurkamilah (English Department, Universitas Negeri Surabaya, 2023)
The present study aimed to describe the implementation of content-based instruction in a microteaching course attended by 28 pre-service teachers of the Biology and Mathematics Education study program. The study regards the importance of ensuring the readiness of 21st-century teachers especially in a class where content-based instruction was implemented. The study, therefore, focuses on the pre-service teachers’ English proficiency in using the target language for teaching subjects (i.e. biology and mathematics) and their skill in operating technology. The data were gathered using a questionnaire that was distributed online. The study found that 1) most respondents are aware of the importance of mastering English for carrying out learning; 2) despite the positive view, none of the respondents are confident that they are lacking English proficiency. Furthermore, 3) the respondents mostly think that they have problems when writing the materials in English, but 4) it was found that they are ready to use English when delivering the materials in the classroom. 5) Most respondents find grammar difficult to deal with, followed by speaking. In regards to the skill in using technology, the study found that 6) most respondents identify themselves as skilled in using technology, and it is supported by the variety of technologies used for teaching and making media. The implication of this study is for policymakers to strengthen course learning outcomes for English subjects.